The ridiculous in Plato - Casertano, Giovanni (Revista Archai, 2020)
What is it that produces laughter? Or a smile, since, in fact, the verb Î³ÎµÎ»Î¬Ï‰ has both meanings? Because for someone to laughs or to smile, it requires to be in the company of others, and involved in a certain situation which somehow sparks in us that kind of reaction. This note will provide a sketch for a research on the various situations in which characters laugh or smile in the Platonic dialogues. There is a ridiculous situation that emerges in a discussion, when the interlocutors speak by themselves without taking into account what the other says (e.g. Euthydemus, Gorgias); another ridiculous situation emerges involuntarily from an intervention or remark from one of the interlocutors (e.g. Phaedrus, Phaedo); another more subjective one emerges from certain behaviors in particular situations (e.g. Republic, Symposium). Moreover, there are interesting indications about the very nature of the ridiculous and the proper way to use it in comedy or in the interactions between people (e.g. Philebus, Laws).